2005
DOI: 10.1007/s00423-005-0011-7
|View full text |Cite
|
Sign up to set email alerts
|

Functional anatomy of the recurrent and superior laryngeal nerve

Abstract: The increased knowledge in neurolaryngology provides the basis for a selective neuromonitoring to lower the risk of laryngeal paralyses after thyroid surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 32 publications
0
10
0
3
Order By: Relevance
“…posterior cricoarytenoid (PCA) muscles receive any kind of nerve fibers from posterior division of the ILN. These fibers contribute innervations of PCA muscle [14, 15]. On the other hand, Maranillo et al [16] have reported that PCA muscles, the only abductor muscle of the larynx receive motor fiber from anterior division of the ILN.…”
Section: Discussionmentioning
confidence: 99%
“…posterior cricoarytenoid (PCA) muscles receive any kind of nerve fibers from posterior division of the ILN. These fibers contribute innervations of PCA muscle [14, 15]. On the other hand, Maranillo et al [16] have reported that PCA muscles, the only abductor muscle of the larynx receive motor fiber from anterior division of the ILN.…”
Section: Discussionmentioning
confidence: 99%
“…HIs work on the recurrent laryngeal nerve is remembered in the eponymous ansa Galeni , the nervous loop between the posterior branch of the recurrent laryngeal nerve and the internal branch of the superior laryngeal nerve (Kruse et al. ). (For further reading on Galen's experiments on the nervous system, see Wickens, .)…”
Section: The Greco‐arabic Canonmentioning
confidence: 99%
“…He challenged his onlookers to match his surgical dexterity, as when he transiently ligated the recursive (recurrent laryngeal) nerves of a pig to demonstrate their role in generating the pig's squeal. HIs work on the recurrent laryngeal nerve is remembered in the eponymous ansa Galeni, the nervous loop between the posterior branch of the recurrent laryngeal nerve and the internal branch of the superior laryngeal nerve (Kruse et al 2006). (For further reading on Galen's experiments on the nervous system, see Wickens, 2015.)…”
Section: The Alexandrian Physiciansmentioning
confidence: 99%
“…Meist handelt es sich um 2, seltener um 3 Äste des NLR, die sich aus dem Hauptstamm meist kranial der Kreuzungsstelle mit der Arterie aufteilen, bevor sie in den Kehlkopf einmünden [5,12,15,31].…”
Section: Anatomie Des Nlrunclassified